A novel assay of neutrophil extracellular trap (NET) formation identifies anti-IL-8 therapies to reduce disseminated intravascular coagulation and mortality in the intensive care unit. (2020) - Abrams, Simon; Morton, Ben; Alhamdi, Yasir; Alsabani, Mohmad; Cheng, Zhenxing; Lane, Steven
No abstract available